(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The impact of the global economic crisis is different Towards different countries. It depends on how each country is integrated into the world economic process, which includes the country’s economic dependence on export-import, existence of transnational companies, and the economic situation in neighboring countries. Its geopolitical location is also important, if the government has worked out economic threat mechanisms and measures. One of the strategic goals of the ongoing reforms in the country should be the root transformation of the economy. We must not forget that modernization of economy first means efficiency of governance management and enterprise management. It is very important to implement the complex management of the economy, which means the integration of macroeconomic and microeconomic management. Considering future demands and interests. As for Georgia, it must have a clearly defined anti-crisis program as a prevention of expected crises and, therefore, to avoid its negative consequences. The main place in the anti-crisis program should be the development of national production and replacement of imported products with local goods. It is necessary to develop a monetary credit policy that will support minimal bank interest rates to stimulate business development and create new jobs.